DESAIN PEMBENTUKAN KARAKTER DAN PENGEMBANGAN DIRI SISWA MELALUI PROGRAM MORNING ACTIVITY DI SDIT AL IBRAH GRESIK - Zuli Dwi Rahmawati; Muchamad Suradji (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2020)
This study aims to: find out the implementation of the Morning Activity program, the design of character formation through the Morning Activity program and the results of the design of character formation through the Morning Activity program at SDIT Al Ibrah Gresik. This research includes field research (field research) with qualitative descriptive method, case study approach, with observation, interview and documentation techniques. From the results of this study, it can be seen that the implementation of the morning activity program runs well, each morning activity contains elements of character formation in each student and the design of character formation through the morning activity program at Al Ibrah Gresik Islamic Primary School is a religious character, honest, tolerance, discipline, hard work, creative, independent, curiosity, and love to read.